1518 The Use of OrthoPathway, Decision Support Software, To Reduce Variation in Practice, Optimise Patient Care and Reduce Face-To-Face Appointments in Trauma and Orthopaedics. (12th October 2021) - Jones, M; Griffiths-Jones, W
Abstract: Introduction: Musculoskeletal problems account for 3.5million Emergency Department attendances annually. Front-line staff are under pressure, faced with complex decisions with limited supportive tools. Without adequate support there is greater variation in practice, poor patient outcomes, longer Emergency Department stays and unnecessary follow-up. OrthoPathway is a web application that enables the production of editable decision support pathways. We have published over 50 Consultant designed, locally approved, interactive pathways. Patient-facing staff can use these to follow national guidelines, by answering questions to establish appropriate treatments. Method: New and follow-up fracture clinic patients were audited over a one-week period. Clinic letters and clerking documents were analysed to identify the diagnosis and management plan. From information and radiographs available OrthoPathway was used to generate a management plan, used as the audit standard. Results: 78 new patients and 83 follow-up patients were seen in fracture clinic over a one-week period. Clinical pathways were available on OrthoPathway for 42% of new patients and 40% of follow-up patients. Variation in practice was seen in 42% of new patients and 59% of follow-up patients. The associated saving in appointments was 11 and 21 and in the new and follow-up patients, respectively. Conclusions: We have shown that OrthoPathway has the potential to reduce face-to-face appointments by 20%, with its current utilisation. Through the deployment of a full set of pathways we anticipated a reduction of greater than 40%, which is particularly pertinent given the current COVID-19 pandemic. This highlights the benefits of Consultant approved decision support pathways published on OrthoPathway.